Advantages and Disadvantages of Google Classroom in Pythagorean Learning for SMPN I Sindang Students - Barikatun Nabilah; Triana Wulandari; Didik Himmawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study aims to find out the advantages and disadvantages of Google classroom in Phytagoras learning in junior high school students. The method used in this study is qualitative through surveys. Where is the limitation of the problem that will be the object in the research activity. The results showed that online learning using the google classroom application has advantages and disadvantages. The advantages are that learning is more practical, saves time, makes it easier to do tasks and can see the material anywhere and anytime. The disadvantages of Google Classroom are that the learning material is not very understandable, the network is unstable and internet quota constraints, cannot ask the teacher directly if there is material that is not understood.